Cannabinoid receptor type 1 in the aging gut regulates the mucosal permeability via miR-191-5p - Lee, Yunna; Kim, Yuju; Park, Soyeong; Heo, Gwangbeom; Chung, Hae Young; Im, Eunok (Frontiers in Endocrinology, 2023)
Aging is associated with a broad loss of function throughout the body, and gastrointestinal (GI) dysfunction can occur with aging. The endocannabinoid (eCB) system plays a pivotal role in various GI diseases, and alterations in the eCB system have been observed during brain and skin aging. Therefore, we investigated the putative role of the eCB system in aging-related changes in intestine. The expression of cannabinoid receptor type 1 (CB1) was decreased in the small intestine of aged rats compared to that of young rats. Cellular senescence was induced by hydrogen peroxide (H2O2) and hydroxyurea (HU) in rat and human intestinal epithelial cells. Senescent cells showed reduced transepithelial electrical resistance (TEER) values and decreased expression of ZO-1, indicating increased intestinal permeability, which is tightly regulated by the CB1 signaling. In silico miRNA analysis suggested that ZO-1 was a direct target gene of miR-191-5p. Increased expression of miR-191-5p by HU was restored by CB1 agonist ACEA co-treatment.Moreover, NF-κB p65 activation was associated with CB1-related miR-191-5p signaling. In conclusion, aging-induced CB1 reduction leads to increased intestinal permeability and decreased ZO-1 expression via upregulation of miR-191-5p and NF-κB p65 activation. Taken together, these results suggest that CB1 signaling may be a useful strategy to reduce intestinal permeability in aging-related and other inflammatory conditions in the gut.